Investigation of thin-walled column with variable i-section stability using finite element method/Plonasienės kintamojo dvitėjo skerspjūvio kolonos stabilumo tyrimas baigtinių elementų metodu - Samofalov, Michail; Kačianauskas, Rimantas (Journal of Civil Engineering and Management, 2000)
Thin-walled structures are widely used in building construction. Stability analysis [1–10] is of major importance to the design of thin-walled structures. This paper deals with the stability analysis of the thin-walled tapered column [11–18]. The aim is to investigate the influence of variation of the web height on the stability of column and combined action of axial force and plane bending moment. Critical state is defined by stability surface obtained by numerical experiments using the finite element method. Mathematical model of the linearised stability problem is presented as algebraic eigenvalue problem (1), where eigenvalues express the critical loading factor (2). Analytical solutions are known for particular cases of separate loading (4), (5). In this paper, the column with variable I-section is presented as assemblage of beam elements with constant section. Thin-walled beam element has 14 degrees of freedom (Fig 1), including linear displacements, rotations and warping displacements. Variation of cross-section of the column (Fig 2) is defined by relative height of web alb, were a and b are the height at the ends of column. Critical state is described by stability surface obtained using numerical experiments. Stability surface presents in the space of relative variation of height a/b, relative length and relative critical force  and bending moment . Variation of section influences the critical bending moment  only. The influence of finite element number on the  with different relative height of web a/b is investigated numerically (Fig 3), and its variation of stability surface is presented in Fig 4. The numerical results show that variation of critical moment  to relative web height a/b is linear (Fig 5). The shapes of buckling modes are presented in Fig 6. Variation of stability surface to relative length (6) is presented in Figs 7 and 8 and expressed by the simple expression (6) constructed on the basis of numerical experiments. Finally, the stability model (1) is compared with nonlinear calculations performed using program ANSYS [19] and shell finite elements (Figs 9 and 10).Article in Lithuanian.First Published Online: 26 Jul 2012